A lithium ion battery
By adjusting the density of the electrolyte and lithium salt concentration, combining a variety of lithium salt composites and functional additives, the problem of high cost of lithium-ion batteries is solved, and the battery performance optimization and cost reduction are achieved.
Patent Information
- Application Number
- CN202210899531.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-28
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-07-28
AI Technical Summary
The prior art is difficult to reduce the cost of lithium-ion batteries on the basis of ensuring the performance of lithium-ion batteries, especially the reduction of lithium salt concentration in the electrolyte.
By adjusting the density of the electrolyte, the lithium salt concentration and the surface density of the active material layer on the positive electrode current collector, it meets the specific relationship, reduces the concentration of lithium salt in the electrolyte, and adopts a variety of lithium salt composites and functional additives to optimize battery performance.
On the basis of ensuring the performance of lithium-ion batteries, the concentration of lithium salt in the electrolyte is reduced, the cost of the battery is effectively reduced, and the wetting property of the electrolyte and the energy density of the battery are improved.
Smart Images

Figure BDA0003770369910000021 
Figure BDA0003770369910000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery preparation, and in particular relates to a lithium ion battery. Background Art
[0002] With the global energy transformation and upgrading and the continuous improvement of carbon emission requirements, the popularity and development prospects of the new energy vehicle industry continue to rise. The vigorous development of electric vehicles is also constantly driving the rapid growth of demand for power lithium batteries, while the requirements for battery range and cost are also getting higher and higher. At present, the main development direction of lithium-ion batteries is high energy, high safety and low cost. Among them, the cost issue has always been the focus of consumers. The reduction of battery costs will promote the rapid promotion and application of electric vehicles that rely on lithium-ion technology. However, due to the skyrocketing prices of lithium battery raw materials, downstream costs have risen sharply, so the cost of batteries has continued to rise, and cost control has become one of the issues focused on by the battery industry.
[0003] Electrolyte is one of the four key materials of lithium batteries. It is the carrier of ion transmission in the battery. It plays the role of conducting lithium ions between the positive and negative electrodes. It has an important impact on the energy density, specific capacity, operating temperature range, cycle life, safety performance, etc. of lithium batteries. In power batteries, electrolyte accounts for about 10%-15% of the total cost. The electrolyte mainly includes lithium salts, solvents and additives. Generally speaking, lithium salts account for about 50% of the total cost of the electrolyte, organic solvents account for about 25%, and additives account for about 25%. Therefore, reducing the concentration of lithium salts in the electrolyte, reducing the amount of lithium salts used, while increasing the energy density of the battery cell and taking into account the electrochemical performance of the battery cell has become one of the research hotspots and difficulties. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the prior art that it is difficult to reduce the cost of lithium-ion batteries while ensuring the performance of lithium-ion batteries, thereby providing a lithium-ion battery.
[0005] To this end, the present invention provides the following technical solutions.
[0006] The present invention provides a lithium ion battery, comprising a positive electrode plate and an electrolyte, wherein the positive electrode plate comprises a positive electrode current collector and an active material layer disposed on the positive electrode current collector, wherein the density of the electrolyte, the concentration of the lithium salt in the electrolyte and the surface density of the active material layer disposed on the positive electrode current collector satisfy the following relationship:
[0007]
[0008] Wherein, ρ is the value of electrolyte density, in g / ml;
[0009] c is the value of lithium salt concentration in the electrolyte, in mol / L;
[0010] A ρ The density of the active material layer on the positive electrode current collector is expressed in mg / cm 2 ;
[0011] The concentration of lithium salt in the electrolyte does not exceed 0.8 mol / L.
[0012] The electrolyte further includes a first solvent;
[0013] Preferably, the density of the first solvent is not higher than 1.0 g / ml.
[0014] The first solvent includes at least one of a carboxylate solvent and an ether solvent;
[0015] Preferably, the carboxylate solvent includes at least one of methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, ethyl butyrate, n-butyl acetate, isobutyl acetate and propyl propionate;
[0016] Preferably, the ether solvent includes at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, methyl tert-butyl ether and 18-crown-6.
[0017] The density of the electrolyte does not exceed 1.2 g / ml;
[0018] Preferably, the surface density of the active material layer on the positive electrode current collector is not less than 18 mg / cm 2 .
[0019] The electrolyte further includes a second solvent;
[0020] Preferably, the mass ratio of the total mass of the first solvent and the second solvent in the electrolyte to the mass of the lithium salt is not less than 7.
[0021] The density of the second solvent is not higher than 1.6 g / ml;
[0022] Preferably, the second solvent comprises at least one of a linear carbonate solvent and a cyclic carbonate solvent;
[0023] Preferably, the linear carbonate comprises at least one of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, diamyl carbonate, propyl carbonate, chloromethyl isopropyl carbonate, 1-chloroethyl isopropyl carbonate, di-tert-butyl dicarbonate, diphenyl carbonate, dimethyl pyrocarbonate, tetraethyl orthocarbonate, diethyl pyrocarbonate, methyl pentafluorophenyl carbonate, bis(2,2,2-trifluoroethyl) carbonate, methyl trifluoroethyl carbonate, fluoroethyl methyl carbonate, fluorodimethyl carbonate, fluorodiethyl carbonate, fluoroethyl acetate, bis(pentafluorophenyl) carbonate, difluoroethylene carbonate and trifluoropropylene carbonate;
[0024] Preferably, the cyclic carbonate includes at least one of ethylene carbonate, vinylene carbonate, propylene carbonate, vinyl ethylene carbonate, divinyl ethylene carbonate, methylene ethylene carbonate, trimethylene carbonate, tert-butylphenyl carbonate, bis(4-nitrobenzene) carbonate, catechol carbonate, fluoroethylene carbonate, fluoropropylene carbonate, difluoroethylene carbonate and trifluoropropylene carbonate.
[0025] The lithium salt includes a first lithium salt and a second lithium salt;
[0026] Preferably, the first lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide;
[0027] Preferably, the second lithium salt is selected from at least one of lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorophosphate, lithium hexafluoroarsenate, lithium dioxalatoborate, lithium nitrate and lithium 4,5-dicyano-2-(trifluoromethyl)isopyrazole;
[0028] Preferably, the molar ratio of the first lithium salt to the second lithium salt is not less than 1;
[0029] Preferably, the lithium salt comprises lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorophosphate in a molar ratio of (2.5-3.2):(4.3-5.5):(0.8-1.2):(0.8-1.3);
[0030] Preferably, the lithium salt comprises lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorophosphate in a molar ratio of 3:5:1:1.
[0031] The electrolyte further includes a functional additive;
[0032] Preferably, the functional additive includes at least one of vinylene carbonate, ethylene carbonate, propylene carbonate, tris(trimethylsilyl) phosphite, fluoroethylene carbonate, lithium difluorophosphate, ethylene sulfate, methylene methanedisulfonate, lithium 4,5-dicyano-2-(trifluoromethyl)pyrazole, triallyl phosphate, 1,3-propane sultone, succinonitrile, dimethyl sulfone methane, trifluoromethyl phenyl sulfide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluoro(oxalato)borate, and lithium bis(oxalato)borate.
[0033] The mass percentage of the functional additive in the electrolyte does not exceed 5%.
[0034] The active material in the positive electrode active material layer has an olivine structure and a phosphoric polyanion group in its structure.
[0035] The positive electrode active material is lithium iron phosphate LiFePO4 and / or LiFe 1-x M x PO4
[0036] Among them, 0 < x ≤ 1, and M is one or a combination of more than one of Mn, Ni, Co, Ti, Mg, Al, V, Cr, Ge, Sr, Y, Zr, Mo, Sn, and W.
[0037] The lithium ion battery satisfies at least one of (1)-(2),
[0038] (1) The lithium ion battery further includes a negative electrode tab;
[0039] Preferably, the thickness of the negative electrode tab does not exceed 200 μm;
[0040] Preferably, the negative electrode tab is lithium; or,
[0041] The negative electrode tab is a lithium alloy; or,
[0042] The negative electrode tab includes a negative electrode current collector and a negative electrode active material layer provided on the negative electrode current collector;
[0043] Preferably, the negative electrode active material layer includes a negative electrode active material, a conductive agent, and a binder; wherein the negative electrode active layer can be coated on one or both sides of the current collector.
[0044] (2) The lithium ion battery further includes a separator;
[0045] Preferably, the separator is at least one of a polyethylene separator, a polypropylene separator, a composite ceramic separator, a cellulose membrane, a polyester membrane, a polyimide membrane, a polyamide membrane, a spandex membrane, an aramid membrane, a non-woven fabric separator, a porous polymer membrane, and an inorganic composite membrane.
[0046] The technical solution of the present invention has the following advantages:
[0047] 1. The lithium-ion battery provided by the present invention makes the density of the electrolyte in the lithium-ion battery, the concentration of lithium salt in the electrolyte and the surface density of the active material layer arranged on the positive electrode current collector satisfy a certain relationship; the present invention adjusts the concentration of lithium salt in the electrolyte, the surface density of the active material layer and the density of the electrolyte to meet specific requirements, and reduces the concentration of lithium salt in the electrolyte on the basis of ensuring the performance of the lithium-ion battery, thereby effectively reducing the cost of the battery cell; at the same time, the reduction in the concentration of lithium salt reduces the viscosity of the electrolyte and improves the wettability of the electrolyte, which is beneficial to the battery cell size. Under the same injection volume, the injection quality of the electrolyte that meets the relationship is low, thereby reducing the cost of the battery; further, the electrolyte provided by the present invention can also enable the lithium-ion battery to have a good energy density. The lithium-ion battery provided by the present invention meets the conventional charging and discharging and rate performance requirements on the basis of reducing the amount of electrolyte injection and the cost of the battery, and the electrolyte conductivity is relatively appropriate.
[0048] Furthermore, the present invention can reduce the concentration of lithium salt in the electrolyte, reduce the cost of the electrolyte, and optimize the battery's charging, discharging, and rate cycling performance by making the lithium salt concentration in the electrolyte, the electrolyte density, and the active material layer density satisfy a specific relationship.
[0049] 2. The lithium-ion battery provided by the present invention can add a first solvent with a density not higher than 1.0 g / ml to the electrolyte, so that the electrolyte has a lower density, the injection quality is reduced, and the lithium-ion battery has a higher energy density.
[0050] 3. The lithium-ion battery provided by the present invention adopts a composite method of multiple lithium salts, especially the lithium salts include lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorophosphate in a molar ratio of 3:5:1:1. The composite lithium salt helps to form the SEI film, optimize the SEI film structure, improve the electrical performance of the battery cell, and meet the charge, discharge and rate requirements of the battery. DETAILED DESCRIPTION
[0051] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0052] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0053] Example 1
[0054] This embodiment provides a 5Ah lithium-ion battery, including an electrolyte, a positive electrode sheet, a negative electrode sheet and a separator;
[0055] The electrolyte includes 8.96g of a first solvent, 5.97g of a second solvent, 1.71g of a lithium salt and 0.36g of a functional additive, and the density of the electrolyte at 22.6°C is 1.1693g / mL; wherein the first solvent includes ethyl propionate and propyl propionate in a mass ratio of 2:4, the second solvent includes ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a mass ratio of 3:1, and the mass ratio of the first solvent to the second solvent is 3:2; the ratio of the total mass of the first solvent and the second solvent to the mass of the lithium salt is 8.7; the lithium salt includes lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorophosphate, and the concentrations in the electrolyte are 0.21mol / L, 0.35mol / L, 0.07mol / L and 0.07mol / L, respectively; the functional additive is vinylene carbonate (VC), and the mass fraction of the functional additive in the electrolyte is 2.12%.
[0056] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode active material is LiFePO4. The positive electrode active material layer includes LiFePO4, conductive agent carbon black and binder PVDF in a mass ratio of 97:1.6:1.4. The surface density of the positive electrode active material layer is 22 mg / cm 2 , compacted density 2.60g / cm 3 .
[0057] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, wherein the negative electrode active material layer includes artificial graphite, conductive agent carbon black and binder CMC in a mass ratio of 95.7:1:3.3, the negative electrode active layer is coated on a single side of the current collector, and the thickness of the negative electrode sheet after rolling is 65μm.
[0058] The diaphragm is a ceramic diaphragm, including a PE diaphragm substrate and an aluminum oxide coating coated on the diaphragm substrate, and the thickness of the aluminum oxide coating is 2 μm.
[0059] In this embodiment The ratio is 0.037.
[0060] Example 2
[0061] This embodiment provides a 5Ah lithium-ion battery, including an electrolyte, a positive electrode sheet, a negative electrode sheet and a separator;
[0062] The electrolyte includes 9.01g of a first solvent, 6.02g of a second solvent, 1.48g of a lithium salt and 0.358g of a functional additive, and the density of the electrolyte at 22.6°C is 1.1606g / mL; wherein the first solvent includes ethyl propionate and propyl propionate in a mass ratio of 2:4, the second solvent includes ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a mass ratio of 3:1, and the mass ratio of the first solvent to the second solvent is 3:2; the ratio of the total mass of the first solvent and the second solvent to the mass of the lithium salt is 10.2; the lithium salt includes lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorophosphate, and the concentrations in the electrolyte are 0.18mol / L, 0.3mol / L, 0.06mol / L and 0.06mol / L, respectively; the functional additive is vinylene carbonate (VC), and the mass fraction of the functional additive in the electrolyte is 2.12%.
[0063] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode active material is LiFePO4. The positive electrode active material layer includes LiFePO4, conductive agent carbon black and binder PVDF in a mass ratio of 97:1.6:1.4. The positive electrode active material layer density is 22 mg / cm 2 , compacted density 2.60g / cm 3 .
[0064] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector. The negative electrode active material layer includes artificial graphite, conductive agent carbon black and binder CMC in a mass ratio of 95.7:1:3.3. The negative electrode active layer is coated on a single side of the current collector. After rolling, the thickness of the negative electrode sheet is 65μm.
[0065] The diaphragm is a ceramic diaphragm, including a PE diaphragm substrate and an aluminum oxide coating coated on the diaphragm substrate, and the thickness of the aluminum oxide coating is 2 μm.
[0066] In this embodiment The ratio is 0.032.
[0067] Example 3
[0068] This embodiment provides a 5Ah lithium-ion battery, including an electrolyte, a positive electrode sheet, a negative electrode sheet and a separator;
[0069] The electrolyte includes 9.10g of a first solvent, 6.07g of a second solvent, 1.22g of a lithium salt and 0.355g of a functional additive, and the density of the electrolyte at 22.6°C is 1.1528g / mL; wherein the first solvent includes ethyl propionate and propyl propionate in a mass ratio of 2:4, the second solvent includes ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a mass ratio of 3:1, and the mass ratio of the first solvent to the second solvent is 3:2; the ratio of the total mass of the first solvent and the second solvent to the mass of the lithium salt is 12.4; the lithium salt includes lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorophosphate, and the concentrations in the electrolyte are 0.15mol / L, 0.25mol / L, 0.05mol / L and 0.05mol / L, respectively; the functional additive is vinylene carbonate (VC), and the mass fraction of the functional additive in the electrolyte is 2.12%.
[0070] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode active material is LiFePO4. The positive electrode active material layer includes LiFePO4, conductive agent carbon black and binder PVDF in a mass ratio of 97:1.6:1.4. The positive electrode active material layer density is 22 mg / cm 2 , compacted density 2.60g / cm 3 .
[0071] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer attached to the negative electrode current collector, wherein the negative electrode active material layer includes artificial graphite, conductive agent carbon black and binder CMC in a mass ratio of 95.7:1:3.3, the negative electrode active layer is coated on a single side of the current collector, and the thickness of the negative electrode sheet after rolling is 65μm.
[0072] The diaphragm is a ceramic diaphragm, including a PE diaphragm substrate and an aluminum oxide coating coated on the diaphragm substrate, and the thickness of the aluminum oxide coating is 2 μm.
[0073] In this embodiment The ratio is 0.026.
[0074] Comparative Example 1
[0075] This comparative example provides a 5Ah lithium-ion battery, including an electrolyte, a positive electrode sheet, a negative electrode sheet and a separator;
[0076] The electrolyte includes 9.186g of a first solvent, 6.12g of a second solvent, 2.21g of a lithium salt and 0.38g of a functional additive, and the density of the electrolyte at 22.6°C is 1.2315g / mL; wherein the first solvent includes ethyl propionate and propyl propionate in a mass ratio of 2:4, the second solvent includes ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a mass ratio of 3:1, and the mass ratio of the first solvent to the second solvent is 3:2; the ratio of the total mass of the first solvent and the second solvent to the mass of the lithium salt is 6.93; the lithium salt includes lithium hexafluorophosphate, and the concentration in the electrolyte is 1 mol / L; the functional additive is vinylene carbonate (VC), and the mass fraction of the functional additive in the electrolyte is 2.12%. The positive electrode sheet includes a current collector and a positive electrode active material layer attached to the current collector. The positive electrode active material is LiFePO4. The positive electrode active material layer includes LiFePO4, conductive agent carbon black and binder PVDF in a mass ratio of 97:1.6:1.4. The positive electrode active material layer density is 22 mg / cm 2 , compacted density 2.60g / cm 3 .
[0077] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer attached to the negative electrode current collector. The negative electrode active material layer includes artificial graphite, conductive agent carbon black and binder CMC in a mass ratio of 95.7:1:3.3. The negative electrode active layer is coated on a single side of the current collector. After rolling, the thickness of the negative electrode sheet is 65μm.
[0078] The diaphragm is a ceramic diaphragm, including a PE diaphragm substrate and an aluminum oxide coating coated on the diaphragm substrate, and the thickness of the aluminum oxide coating is 2 μm.
[0079] In this comparative example The ratio is 0.056.
[0080] Test example
[0081] This test example provides the performance test results of the lithium-ion batteries and electrolytes of various embodiments and comparative examples, as follows:
[0082] Test method for battery cycle performance under normal temperature and high temperature conditions: Each battery is cycled 1000 times, and the battery capacity retention rate before and after the cycle is calculated. Among them, the normal temperature test conditions are: 1.0C rate discharge, 1.0C rate charge, voltage range 2.5~3.65V, temperature 25±5℃. The high temperature test conditions are: 1.0C rate discharge, 1.0C rate charge, voltage range 2.5~3.65V, temperature 45±5℃.
[0083] The test method for high temperature storage performance of batteries: After fully charging the battery cell at 1C constant current and constant voltage and storing it at 60±5℃ for 30 days, calculate the battery capacity retention rate before and after storage.
[0084] The above test results are shown in Table 1.
[0085] Table 1 Test results of various embodiments and comparative examples
[0086]
[0087] When the lithium salt concentration in the electrolyte of Comparative Example 1 is 1 mol / L, the cost of the electrolyte of Comparative Example 1 is about 20% higher than that of Example 1 when the lithium salt concentration in the electrolyte is 0.7 mol / L. The battery prepared by the present invention significantly reduces the cost while ensuring the battery performance.
[0088] Furthermore, compared with the battery prepared in Comparative Example 1, the battery prepared in the present invention has better cycle performance and higher energy density, meets the conventional charge and discharge and rate performance requirements, the conductivity of the electrolyte also meets the use requirements, the lithium salt concentration in the electrolyte is lower, and the cost is also lower.
[0089] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A lithium-ion battery, comprising a positive electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and an active material layer disposed on the positive electrode current collector, characterized in that: The electrolyte includes a lithium salt, a first solvent and a second solvent, wherein the first solvent includes at least one of a carboxylic acid ester solvent and an ether solvent; the density of the electrolyte, the concentration of the lithium salt in the electrolyte, and the surface density of the active material layer disposed on the positive electrode current collector satisfy the following relationship: 0< c·ρ ≤0.05 A ρ Wherein, ρ is the value of electrolyte density, in g / ml; c is the value of lithium salt concentration in the electrolyte, in mol / L; A ρ is the density of the active material layer on the positive electrode current collector, in mg / cm 2 ; The concentration of lithium salt in the electrolyte does not exceed 0.8 mol / L.
2. The lithium-ion battery according to claim 1, characterized in that The density of the first solvent is not higher than 1.0 g / ml.
3. The lithium-ion battery according to claim 2, characterized in that: The carboxylate solvent includes at least one of methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, ethyl butyrate, n-butyl acetate, isobutyl acetate and propyl propionate.
4. The lithium-ion battery according to claim 2, characterized in that: The ether solvent includes at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, methyl tert-butyl ether and 18-crown-6.
5. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The density of the electrolyte does not exceed 1.2 g / ml.
6. The lithium-ion battery according to claim 5, characterized in that: The surface density of the active material layer on the positive electrode current collector is not less than 18 mg / cm 2 .
7. The lithium-ion battery according to claim 6, characterized in that: The mass ratio of the total mass of the first solvent and the second solvent in the electrolyte to the mass of the lithium salt is not less than 7.
8. The lithium-ion battery according to claim 1, characterized in that The density of the second solvent is not higher than 1.6 g / ml.
9. The lithium-ion battery according to claim 1, characterized in that: The second solvent includes at least one of a linear carbonate solvent and a cyclic carbonate solvent.
10. The lithium ion battery according to claim 9, characterized in that: The linear carbonate includes at least one of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, diamyl carbonate, propyl carbonate, chloromethyl isopropyl carbonate, 1-chloroethyl isopropyl carbonate, di-tert-butyl dicarbonate, diphenyl carbonate, dimethyl pyrocarbonate, tetraethyl orthocarbonate, diethyl pyrocarbonate, methyl pentafluorophenyl carbonate, bis(2,2,2-trifluoroethyl) carbonate, methyl trifluoroethyl carbonate, fluoroethyl methyl carbonate, fluorodimethyl carbonate, fluorodiethyl carbonate, fluoroethyl acetate, bis(pentafluorophenyl) carbonate, difluoroethylene carbonate and trifluoropropylene carbonate.
11. The lithium ion battery according to claim 9, characterized in that: The cyclic carbonate includes at least one of ethylene carbonate, vinylene carbonate, propylene carbonate, vinyl ethylene carbonate, divinyl ethylene carbonate, methylene ethylene carbonate, trimethylene carbonate, tert-butylphenyl carbonate, bis(4-nitrobenzene) carbonate, catechol carbonate, fluoroethylene carbonate, fluoropropylene carbonate, difluoroethylene carbonate and trifluoropropylene carbonate.
12. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The lithium salt includes a first lithium salt and a second lithium salt.
13. The lithium ion battery according to claim 12, characterized in that: The first lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.
14. The lithium ion battery according to claim 12, characterized in that: The second lithium salt is selected from at least one of lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorophosphate, lithium hexafluoroarsenate, lithium dioxalatoborate, lithium nitrate and lithium 4,5-dicyano-2-(trifluoromethyl)isopyrazole.
15. The lithium ion battery according to claim 12, characterized in that: The molar ratio of the first lithium salt to the second lithium salt is not less than 1.
16. The lithium ion battery according to claim 12, characterized in that: The lithium salt includes lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorophosphate in a molar ratio of (2.5-3.2):(4.3-5.5):(0.8-1.2):(0.8-1.3).
17. The lithium ion battery according to claim 12, characterized in that: The lithium salt includes lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorophosphate in a molar ratio of 3:5:1:
1.
18. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The electrolyte further includes a functional additive.
19. The lithium ion battery according to claim 18, characterized in that The functional additives include at least one of vinylene carbonate, ethylene carbonate, propylene carbonate, tris(trimethylsilyl)phosphite, fluoroethylene carbonate, lithium difluorophosphate, vinyl sulfate, methylene disulfonate, lithium 4,5-dicyano-2-(trifluoromethyl)isopyrazole, triallyl phosphate, 1,3-propane sultone, succinonitrile, dimethanesulfonylmethane, trifluoromethylphenyl sulfide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate and lithium dioxalatoborate.
20. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The active material in the positive electrode active material layer has an olivine structure and a phosphate polyanion group.
21. The lithium ion battery according to any one of claims 1 to 4, characterized in that: Satisfies at least one of (1)-(2), (1) The lithium-ion battery also includes a negative electrode plate; (2) The lithium-ion battery further includes a separator.
22. The lithium ion battery according to claim 21, characterized in that The thickness of the negative electrode plate does not exceed 200 μm.
23. The lithium ion battery according to claim 21, characterized in that The diaphragm is at least one of a polyethylene diaphragm, a polypropylene diaphragm, a composite ceramic diaphragm, a cellulose membrane, a polyester membrane, a polyimide membrane, a polyamide membrane, a spandex membrane, an aramid membrane, a non-woven fabric diaphragm, a porous polymer membrane and an inorganic composite membrane.
Citation Information
Patent Citations
Preparation method of lithium ion battery and lithium ion battery
CN108039449A
Low-concentration lithium salt electrolyte and lithium secondary battery containing same
CN109935908A